FRI0431 Venous and Arterial Thrombosis in Sle: Differences in Natural History. (10th June 2014) - Hickman, K.; Magder, L.; Petri, M.
Abstract : Background: Thrombosis is increased in SLE due to disease activity and co-morbid factors including antiphospholipid antibodies. We separately investigated the natural history of venous vs. arterial thrombosis. Methods: 2250 patients were enrolled in a prospective cohort; 334 had a thrombotic event before cohort entry or diagnosis of SLE. For ALL thrombosis, age over 60 yrs, male gender, African-American ethnicity, SLEDAI greater than 3, and prednisone greater than 0 were risk factors. In general, rates of venous thrombosis were fairly constant, while rates of arterial thrombosis increased with age. Results: See Table 1 . Conclusions: Prevention of venous thrombosis remains important throughout the course of SLE. Prevention of arterial thrombosis becomes more important later in the disease course. Disease activity is more of a risk factor for arterial thrombosis while prednisone is a risk factor for both venous and arterial thrombosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3776